Association between menstrual-related disorders and sexually transmitted infections: A nationwide cross-sectional study in Japan - Tatsuya Yoshihara; So Owada; Harumasa Arita; Akiko Nakagomi; Kota Tanaka; Yosuke Ono; Osamu Yoshino (PLoS ONE, 2026)
Background To investigate the association between menstrual-related disorders and sexually transmitted infections (STI) among young women in Japan, and to examine differences according to disorder type and hormonal therapy use. Methods This cross-sectional study used the Japan Medical Data Center Claims Database and included women younger than 40 years who had at least one healthcare visit in 2023. Menstrual-related disorders were defined as endometriosis or dysmenorrhea based on ICD-10 codes. The prevalence of five STIs—gonorrhea, genital chlamydia infection, trichomoniasis, genital herpes, and other sexually transmitted conditions—was compared between women with and without menstrual-related disorders. Subgroup analyses were conducted for endometriosis, dysmenorrhea, and hormonal therapy (low-dose estrogen–progestin combinations or dienogest). Prevalence ratios (PR) and prevalence differences (PD) with 95% confidence intervals (CI) were estimated. Results Among 3,440,929 women, 257,897 (7.5%) had menstrual-related disorders. All STI were substantially more prevalent in this group than in women without menstrual-related disorders, with PRs ranging from 4.31 to 5.29. Endometriosis showed the highest prevalence, particularly for genital chlamydia infection (4.98%; PR 7.44). Dysmenorrhea was also associated with consistently elevated STI prevalence. Among women with menstrual-related disorders, STI prevalence differed only slightly according to hormonal therapy use, with differences generally within one percentage point. Conclusion Menstrual-related disorders were strongly associated with increased diagnosis of STI in Japanese young women. These findings highlight the importance of integrating STI screening and reproductive health education into routine gynecologic care for women with endometriosis or dysmenorrhea. The influence of healthcare-seeking behavior and diagnostic patterns should be considered when interpreting claims-based STI data.